Determinants of Accuracy of Minimum Standards of Anc Visits in Midwife Self Practices - Ni Luh Made Asmariani; Putu Sukma Megaputri (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Sixtime visits for antenatal care according to the World Health Organization guidelines spread over trimesters 1, 2 and 3. The timing of these visits is important so that pregnant women get maximum health checks and early detection can be carried out. This research method is quantitative with a cross sectional approach. The independent variable is the determinant of the mother in terms of internal factors such as age, education, parity and then the dependent variable is the accuracy of the ANC visit to the independent midwife practice. The sampling technique in this study was purposive sampling with a total sample of 64 respondents. The results of the study reported that the determinants of risk factors that could increase the accuracy of ANC visits were the mother's recent high school education (high school and college) with a p value <0.05 and parity of the mother as a primigravida with a p value <0.05. The conclusion is that the accuracy of the mother's visit in carrying out the ANC examination is based on the last education and parity of the mother.